Determination of the spin polarization of RFe2 (R = Dy, Er, Y) by point contact Andreev reflection - Morrison, C; Wang, D; Bowden, G; Ward, R; de Groot, P (2012)
Epitaxially grown intermetallic RFe 2 (R Dy, Er, Y) thin films have been studied by point contact Andreev reflection. Spin polarization values were extracted by fitting normalized conductance curves for mechanical Nb/RFe 2 point contacts, using a modified Blonder-Tinkham-Klapwijk model. Good agreement is found between this model and the experimentally obtained data. Extracted values of spin polarization, which are close to the spin polarization of Fe, reveal no variation with the rare earth component for the measured intermetallic compounds. This suggests that using this technique we probe the Fe sub-lattice, and that this lattice drives spintronic effects in these compounds. © 2012 American Institute of Physics.